2015
DOI: 10.1245/s10434-015-4886-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury After Radical Cystectomy for Bladder Cancer is Associated with Chronic Kidney Disease and Mortality

Abstract: AKI is not only commonly encountered after radical cystectomy but is also associated with higher CKD rates and mortality. There is a critical need for strategies to increase the identification of patients at risk of postoperative AKI, and to improve the management of patients, with an aim toward preventing AKI and improving the treatment of AKI once it occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Besides, partial or radical cystectomy are standard surgical procedure for patients with bladder cancer. A cohort study, including 886 patients who underwent radical cystectomy for bladder cancer, found that 33.1% developed AKI in the first week after surgery . All of these factors contributed to the high incidence of AKI in patients with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, partial or radical cystectomy are standard surgical procedure for patients with bladder cancer. A cohort study, including 886 patients who underwent radical cystectomy for bladder cancer, found that 33.1% developed AKI in the first week after surgery . All of these factors contributed to the high incidence of AKI in patients with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study, including 886 patients who underwent radical cystectomy for bladder cancer, found that 33.1% developed AKI in the first week after surgery. 15 All of these factors contributed to the high incidence of AKI in patients with bladder cancer. The development of AKI is also common in patients with leukemia and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have highlighted the role of AKI on mortality in patients with hematologic malignancies receiving induction therapy, diffuse large B‐cell lymphoma, gastric cancer, bladder cancer, and lung cancer . Additionally, the increase in mortality according to the development of AKI has not been observed in all studies due to the different patients' conditions, including overall severity, and functional status …”
Section: Introductionmentioning
confidence: 99%